The Relationship Between Work Motivation and Work Involvement in Sales Marketing in East OKU Regency - Atika Dewi; Desy Arisandy (Universitas Batanghari, 2022)
Human resources are an essential asset for the progress of the company. This study aims to determine the Relationship Between Work Motivation and Work Involvement in Sales Marketing in East OKU Regency. The quantitative research method used is a questionnaire to answer the problem formulation. The population in this study was 180 sales marketing people in East Oku Regency. The data analysis method in this study was carried out in two stages, 1) Assumption / Prerequisite Test (normality and linearity test) and 2) Hypothesis Test. The results showed a significant relationship between Work Motivation and Work Involvement in Sales Marketing in OKU Timur. Simple regression results showed acceptance of the proposed hypothesis. The value of the correlation coefficient r = 0.289 or 28.9% with the significant value (P) = 0.001 < 0.01, meaning it shows a very significant relationship between Work Motivation and Work Engagement.